Influence of Pore Space Hierarchy on the Efficiency of an Acetylcholinesterase‐Based Support for Biosensorics. Issue 4 (29th April 2020) - Kohns, Richard; Anders, Nicole; Enke, Dirk; Tallarek, Ulrich
Abstract: The influence of a hierarchically structured pore system of a silica sol–gel support for application as a functional component in an acetylcholinesterase‐based enzyme array, with respect to its efficiency (response time, in particular) is investigated. Careful adjustment of synthesis parameters and a novel drying method allow to prepare monolithic silica sol–gel membranes with monomodal or hierarchical pore structures. These supports enable direct comparison regarding the influence of morphological properties on maximum acetylcholinesterase (AChE) loading by a membrane and on the apparent reaction rate of the AChE‐catalyzed degradation of acetylcholine at identical enzyme loading. It is shown for the first time that the hierarchical, meso‐macroporous material is superior over the monomodal structures (of either mesopores or macropores) regarding combined functionality and transport efficiency, as reflected in the apparent reaction rates. The advantage of the mesopores in a hierarchical system is manifested in higher maximum enzyme loading than for purely macroporous material, while the presence of macropores results in less obstructed transport that for a purely mesoporous material, which in turn reduces the response time. Abstract : It is investigated how a hierarchical morphology of functional membranes affects the apparent reaction rates in the acetylcholinesterase‐catalyzed degradation reaction of acetylcholine to choline. Hierarchical, meso‐macroporous membranes can boost performance by combining the advantages of purely mesoporous and purely macroporous membranes, that is, higher enzyme loading and enhanced mass transfer.